2017
DOI: 10.1093/toxsci/kfx177
|View full text |Cite
|
Sign up to set email alerts
|

Editor’s Highlight: Structure-Based Investigation on the Binding and Activation of Typical Pesticides With Thyroid Receptor

Abstract: A broad range of pesticides have been reported to interfere with the normal function of the thyroid endocrine system. However, the precise mechanism(s) of action has not yet been thoroughly elucidated. In this study, 21 pesticides were assessed for their binding interactions and the potential to disrupt thyroid homeostasis. In the GH3 luciferase reporter gene assays, 5 of the pesticides tested had agonistic effects in the order of procymidone > imidacloprid > mancozeb > fluroxypyr > atrazine. 11 pesticides inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The hormone‐dependent proliferation assays (T‐ and E‐Screen) showed that the seven neonicotinoids we tested are unlikely to activate oestrogen receptors and TRs (Figures and ). It has been reported that imidacloprid can have TR agonist effects in a GH3 luciferase reporter gene assay (Xiang et al, ). This observation would appear to contradict the findings we present here; however, upon close scrutiny of the data presented by Xiang and colleagues, the response to imidacloprid in their reporter gene assay was very weak (less than twofold of the control) (Xiang et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hormone‐dependent proliferation assays (T‐ and E‐Screen) showed that the seven neonicotinoids we tested are unlikely to activate oestrogen receptors and TRs (Figures and ). It has been reported that imidacloprid can have TR agonist effects in a GH3 luciferase reporter gene assay (Xiang et al, ). This observation would appear to contradict the findings we present here; however, upon close scrutiny of the data presented by Xiang and colleagues, the response to imidacloprid in their reporter gene assay was very weak (less than twofold of the control) (Xiang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that imidacloprid can have TR agonist effects in a GH3 luciferase reporter gene assay (Xiang et al, ). This observation would appear to contradict the findings we present here; however, upon close scrutiny of the data presented by Xiang and colleagues, the response to imidacloprid in their reporter gene assay was very weak (less than twofold of the control) (Xiang et al, ). Thus, this poor efficiency of interaction with the TR may be insufficient to provoke a physiological response such as cell proliferation in a T‐Screen as we present.…”
Section: Discussionmentioning
confidence: 99%
“…A TH-dependent proliferation assay (T-screen) with GH3 cells was employed to investigate the thyroid disrupting potential of common neonicotinoids, but none of the 7 neonicotinoids tested had any effect on TH-dependent proliferation (200) in the absence of T3. However, Xiang et al (201) showed that IMI exerted agonist effects in a GH3 luciferase reporter gene assay mediated via TR which was further characterized using human TRβ in a Surface Plasmon Resonance biosensor technique to measure binding kinetics. Moreover, in silico molecular docking (MD) analysis predicted that IMI may compete with T3 for binding with TR by forming hydrogen bonds with the imidazole group (202).…”
Section: In Vitro Evidence Of Thyroid Disruptionmentioning
confidence: 99%
“…An alternative hypothesis which has been recently raised, is that they might exert an adverse effect on mammalian neurodevelopment by acting as THD ( Leemans et al., 2019 ). Although TH circulating levels or thyroid gland histology are sometimes altered by pesticides ( Moser et al., 2015 ; Paul et al., 2012 ; Yaglova and Yaglov, 2017 ) these effect do not seems to correlate with a direct binding to TRs, which have only been observed at high concentrations for few compounds ( Xiang et al., 2017 ). It is thus tempting to speculate that some pesticides belong to the second class of chemicals, which interfere with the cellular response to T3 without binding to TRs.…”
Section: Introductionmentioning
confidence: 99%